Merkel Cell Carcinoma Concomitant with Invasive Bowen's Disease: Immunohistochemical Investigation of Tumor-Infiltrating Leukocytes - Hisayuki Tono; Taku Fujimura; Eimei Iwama; Yoshiyuki Kusakari; Sadanori Furudate; Yumi Kambayashi; Takahiro Haga; Akira Hashimoto; Setsuya Aiba (Karger Publishers, 2015)
Merkel cell carcinoma (MCC) is an aggressive, cutaneous, neuroendocrine carcinoma and, in rare cases, occurs with Bowen's disease (BD). In this report, we describe a case of MCC concurrent with invasive BD and compare the profiles of tumor-infiltrating leukocytes in the lesional skin of MCC and invasive BD. Interestingly, immunohistochemical study revealed significant numbers of CD8+ cells and caspase 3-expressing cells in the same areas of invasive BD and MCC. Our present case suggests that MCC concurrent with invasive BD might have a good prognosis because of the substantial number of CD8+ cells in the tumor.